Wood and wood joints : building traditions of Europe, Japan and China - Zwerger, Klaus, 1956- (Birkhäuser, 2015)
"Building with wood as an ecologically viable material is a tradition with a long history. In the most typical method, elements are connected by using wood joints which do not require the assistance of adhesives or metal connectors. By looking at several hundred examples from Japan, China and 18 European countries, this book describes in great detail the history of timber architecture in terms of its technical, aesthetic and ecological dimensions. This thorough study is a mine of information to specialists in this field; it opens up to the craftsman of today what has become an almost forgotten world and provides a fascinating account for the general reader. The new introduction to the third edition reviews developments since the first publication of this book in 1997"--Provided by publisher.